Building Big Profits in Real Estate: A Guide for The New Investor - Timmerson Wade; Caplan Suzanne (American : Wiley, 2004)
Everyday, people just like you have a real chance to make serious money in real estate. All it requires is the discipline to purchase good property and the motivation to make new purchases that will create growing equity. Filled with in-depth insights and practical advice, Building Big Profits in Real Estate will show you the right way to invest in real estate.
A successful stock market investor may need to perform extensive research to make a profit, but becoming a successful real estate investor can be more complex and far more hands-on, especially when you’re just getting started. The good thing about real estate is that it offers more security as well as greater upside potential than any other investment––mainly because the value of property never goes to zero (unlike some recent stocks) and real estate prices often continue to go up even when general economic conditions are soft.
Building Big Profits in Real Estate focuses on the sound strategies that everyone needs to understand before they invest in real estate. It covers important topics, such as analyzing markets, financing your projects, purchasing rental property, managing a real estate portfolio, finding new ways to invest, and understanding wholesale markets. It also reveals some of the most overlooked opportunities in the real estate market, including Section 8 rentals, wholesaling properties, and selling houses on a rent-to-own basis.
Keywords: Real Estate Investment; Real Estate Management; United States; Rental Housing-Management